Análise das relações existentes entre qualidade de vida e qualidade de vida no trabalho através de um modelo de regressão logística - Maier, Rúbia Carla (2012)
The objective of this study was to identify the relationship between the quality of life and quality of working life of employee on the dairy industry using logistic regression. The proposed problem was: What are probabilistic relationships between quality of life and quality of working life? The theoretical referential involved: quality of life, quality of working life and statistical reasoning. The methodological approach was applied, descriptive, qualitative and quantitative. Was used a survey of employees of the dairy industry, which were investigated by simultaneous application of the WHOQOL-100 and an adaptation of the Walton’s model, were interviewed in all 548 employees between men and women. The analyzes had involved: correlation, chi-square and logistic regression. For validating the model estimat ed by logistic regression analysis, it was used the Deviance, Pearson and Hosmer -Lemeshow test. The results in the univariate logistic regression analysis showed that the criteria of QWL have significant influence on QL and the QL domains (except the spiritual domains) have significant influence on QWL. In multivariate logistic regression model, some variables were not as significant as had values above the level of significance (p>0,05). Considering these variables in was estimated a mathematical model, finding the probability of influence between the variables (domains, criteria, QL and QWL). By studying the relationship between these variables was possible to conclude the chances of improvement in the areas of QL that positively influence the QWL, and the criteria of QWL that positively influence the QL, providing the manager a better direction of their investments.